Upaya peningkatan kinerja guru SD Negeri 3 Ngambakrejo dalam membuat perangkat pembelajaran melalui kegiatan supervisi - Ngatini, Ngatini (Universitas Sebelas Maret, 2023)
The main problems that will be solved through this School Action Research are: Efforts to Improve Teacher Performance in Making Learning Devices at SDN 3 Ngambakrejo, Responsibilityrjo District, Grobogan Regency by carrying out supervision activities. The action hypothesis is: If supervision activities are carried out effectively, it is suspected that the teacher's performance in making learning tools will increase. This research is the action of the school principal to improve teacher performance in the process of compiling/making learning tools at SDN 3 Ngambakrejo, Responsibilityrjo District, Grobogan Regency. The research was conducted in four stages and included four activities, namely observation, planning, implementation and monitoring, meaning and reflection as well as revision or planning for the next cycle. Each cycle consists of 3 actions, namely: informing teachers about the procedures for compiling learning tools, providing training in the form of assignments to compiling syllabus, Responsibility Program, Semester Program, KKM, Learning Plans and Analysis to teachers and concluding the material for supervision activities. To monitor the implementation of action research, tools are used in the form of observation sheets and notes to improve teacher performance in making learning tools. Researchers have the role of providing input in every action that will be carried out by the teacher. The results showed that the percentage of teachers who experienced an increase in teacher performance in each supervision activity always increased in each cycle. The average percentage of teachers who made learning tools perfectly, namely cycle I, was 50% and 85.75%. Managerial supervision activities have been proven to improve teacher performance in preparing learning tools. This managerial supervision that is carried out effectively can be used and developed to assist teachers in solving problems encountered in making reports.